Immanent and diffractive critique in scholarship and publication - Bozalek, Vivienne; Romano, Nike (Critical Studies in Teaching and Learning, 2023)
Criticality and critique require careful attention by authors, reviewers,and editors in Critical Studies in Teaching and Learning(CRiSTaL), since they form a central focus of the journal. Conventional views of critique are influenced by unexpressed assumptions that what is needed is an authoritative expert, who from a position of superiority and distance, diagnoses and pronounces on the inadequaciesof the text. This article explores more generative approaches to critique and criticality such as immanent critique and diffractive methodologies. We argue that in order for immanent critique and diffractive methodologies to happen, sensibilities such as attentiveness, response-ability, accountability, generosity,and curiosity are necessary. The final section of the paper considers academic practices of reviewing, writing, reading, pedagogy,and conferencing in relation to immanent critique and diffractive methodologies and the sensibilities we propose which make these forms of critique and criticality possible.